2015
DOI: 10.4236/ajps.2015.65079
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Variation in Flower Size and Flower-Visitor Composition of Two Bumblebee-Pollinated, Spring-Flowering Herbs, <i>Lamium album</i> L. var. <i>barbatum</i> (Lamiaceae) and <i>Meehania urticifolia</i> (Lamiaceae)

Abstract: Geographic variation of flower size is potentially affected by various biotic and abiotic factors such as pollinator size, abundance of nectar robbers, and temperature. To elucidate the effect of geographic variation of flower-visitor fauna on flower size, we investigated two spring-flowering, bumblebee-pollinated herbs, Lamium album L. var. barbatum (seven populations) and Meehania urticifolia (five populations), in central Japan. Flower-size variations were not correlated with altitude (an index of abiotic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionsupporting
confidence: 51%
“…Previous studies that have investigated flower size variations along an altitudinal gradient in mountainous environments have reported corresponding altitudinal variations in, for example, pollinator species composition and nectar robbing frequency (Hattori et al , 2015Nagano et al 2014;Kuriya et al 2015;Zhao & Wang 2015). In this study, we showed that the pattern of flower size variation along an altitudinal gradient differed between two Impatiens species growing in similar habitats.…”
Section: Discussionsupporting
confidence: 51%
“…barbatum (Lamiaceae) is a perennial herb that grows along forest edges throughout East Asia [47]. It produces creamy white, twolipped, entomophilous, and self-incompatible owers [40,41]. The owers are frequently visited by various bumblebee species, and in Japan, the corolla tube length of the owers may correlate with the size (proboscis length and head length) of their bumblebee pollinators.…”
Section: Plant Speciesmentioning
confidence: 99%
“…In addition to bumblebees, honeybees and wild bees have been observed to visit L. album var. barbatum owers, but in Japan bumblebees are their main pollinators [40].…”
Section: Plant Speciesmentioning
confidence: 99%
See 2 more Smart Citations